Boston outrage (House document (Virginia. General Assembly. House of Delegates) ;, 1843)
1842 Proceedings of the Citizens of the Borough of Norfolk on the Boston Outrage, in the case of the runaway slave George Latimer, transmitted by Virginia governor James McDowell to the House of Delegates on February 9, 1843. Latimer was a slave who had escaped to Boston, was discovered and incarcerated in a Boston jail until his freedom was purchased; the proceeding determined that the slave owner's rights had been "invaded." Included were documents from both Virginia and Massachusetts. Of note, various abolitionist groups and policy, as well as social unrest, developed as a result of this case.